Machine learning for tissue diagnostics in oncology: brave new world - Halama, Niels (British journal of cancer, 2019)
Machine learning is an exciting technology with broad application in big data analysis, as well as increasingly in specialised healthcare. As a diagnostic tool in tissue workup and pathology, it has the potential for personalised and stratified approaches, but the limitations and pitfalls need to be better understood and characterised especially in this critical area of medical care.
Gesehen am 07.10.2019